(untitled) (The Agriculturists, 2015)
Introduction of appropriate machinery is one of the major factors for reducing time and labor requirements, production cost and also to help fit another crop in between successive two crops. In this study, performance of the Bangladesh Rice Research Institute (BRRI) developed self-propelled reaper and an imported Chinese reaper were evaluated for rice harvesting and were compared with manual harvesting. The experiment was conducted at BRRI Regional station in Rajshahi and Rangpur during Boro 2012-13. Average field capacity of the BRRI reaper was 0.250 ha/hr and that of Chinese reaper was 0.203 ha/hr. The average field capacity of manual harvesting was 0.004 ha/hr. Labour requirements for rice harvesting including bundle making were 248 man-hr/ha, 69 man-hr/ha and 68 man-hr/ha for manual, Chinese reaper and BRRI reaper, respectively. On an average, 72 and 03% labour was saved by the BRRI reaper over those of manual harvesting and Chinese reaper, respectively. Harvesting costs were saved by BRRI reaper and Chinese reaper about 68 and 61%, respectively over that of manual harvesting. Average fuel consumption of Chinese reaper and BRRI reaper were 0.727 and 0.826 l/hr, respectively. The walking speed of BRRI reaper (3.78 km/hr) was 62% higher than that of Chinese reaper (2.33 km/hr). The purchase price of imported reaper is almost double than that of BRRI reaper. The BRRI reaper was, therefore, considered as a better machine for harvesting rice in Bangladesh. The Agriculturists 2014; 12(2) 142-150